An empirical study on the effect of M&A on banks’ performance & shareholders’ value in the US banking sector - ZENG, WEI YUAN (2013)
This study investigates the impacts of mergers and acquisitions (M&As) on banks’ performance. The focus on a sample of large US banks involved in M&As during the period of 2006 to 2012. An examination of the effects of mergers and acquisitions on banks’ performances is made using the panel data model. The analysis presents evidence that M&A activity has a significant influence on the US banks’ performance. The study involves comparing with bank profitability ratios such as return on equity (ROE) and return on assets (ROA) of both merged banks and non-merged banks. The results indicate that the performances between merged and non-merged banks are different based on ROE and ROA as a measurement; because the former type of banks tend to pursue higher growth, economics of scale and greater capitalisation than non-merged banks. However, results did not show that mergers and acquisitions have a beneficial effect on shareholder’s value as measured by return on equity.